Proses Pembelajaran Melalui Interaksi Edukatif Dalam Pendidikan Islam - Media Gusman (STAI Serdang Lubuk Pakam, 2022)
This study aims to analyze the learning process through educative interactions in Islamic education. This research uses research method library Research. (Library Studies), where the data sources used are books, or research journals related to Educational Interaction. Data collection is of course done with documentation techniques. The results of the study explain that the process of educative interaction is a process that contains a number of norms, all of which the teacher must transfer to students. There are several principles of educative interaction, namely the principle of motivation, the principle of perception, the principle of focus, the principle of integration, the principle of problem solving, the principle of seeking, the principle of learning while working, the principle of social relations, and the principle of individual uniqueness. The attitude of professional educators is not limited to mere technical competence, but also to their personality and character. Learning attitude is very dependent on the teacher as a leader in the teaching and learning process. The attitude of learning is not just an attitude shown to the teacher, but also to the goals to be achieved, subject matter, assignments and others.